Comparison of three isolation systems for the culture of mycobacteria from respiratory and non-respiratory samples. Issue 8 (1st August 2000) - Harris, G; Rayner, A; Blair, J; Watt, B
Abstract : Aims —To compare the recovery of mycobacteria from clinical samples using the MB/BacT rapid culture system with that obtained using egg medium or the Bactec radiometric method. Methods —The three methods were compared using 681 clinical samples (462 respiratory and 219 non-respiratory samples) and eight external quality control strains. Culture media were incubated at 35–37°C for six weeks in the MB/BacT system and for 12 weeks in the Bactec system and on egg medium. Solid media were examined macroscopically once a week and the Bactec vials were read six times in the first two weeks, and then weekly for the next 10 weeks (a growth index > 50 indicated a positive vial). The MB/BacT system positive vials were unloaded from the machine as soon as possible after detection. Confirmation of growth for all systems was by Ziehl-Neelson stained smears. Isolates were identified by a combination of phenotypic and molecular methods. Results —Of the 681 clinical samples, 59 (8.7%) were positive on culture, including 23 strains of Mycobacterium tuberculosis. None of the three systems recovered all of the isolates, but each recovered mycobacteria not detected by either of the other two systems. After six weeks incubation, isolation rates were 87%, 78%, and 90%, and mean times to detection were 13, 19, and nine days for the MB/BacT, egg medium, and Bactec systems, respectively. Although the MB/BacT system was slightly slower than the Bactec system, the biomass was greater, allowing earlier use of molecular probes and earlier inoculation of susceptibility tests. Conclusions —The MB/BacT system provides comparable performance to the Bactec radiometric system, without the problems of disposal of radioactive waste. Optimal recovery is obtained when culture on egg medium is used in conjunction with a rapid culture system.